Training on Developing Website-Based SAPA Science Process Skills Assessment for the Langsa City Science Teacher Working Group - Putri, Mentari Darma; Zatya, Ismi; Saleh, Alfa; Oktaviani, Coryna (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: Science Process Skills (SPS) are important competencies in science learning because they emphasize students' critical, analytical, and practical thinking skills. However, the practice of SPS assessment in schools is still limited, mainly due to the dominance of conventional instruments and the limited use of digital technology.Aims: This community service activity aimed to improve the understanding and skills of junior high school science teachers in Langsa City to develop and implement technology-based SPS assessments.Method: This community service activity was a training and mentoring-based program which consisted of four main stages: socialization, training, technology implementation, and mentoring and evaluation, involving 25 science teachers as participants. This approach not only provided knowledge transfer but also ensured real implementation in the field through practical activities and continuous feedback. The evaluation instruments consisted of pretests and posttests, assessment products (student worksheets, rubrics, and SPS questions), and participant response questionnaires.Results: The results of the activity showed an increase in the average pretest score from 60.4 to 92.8 on the posttest with an N-gain value of 0.8 (high category). In addition, more than 85% of teachers responded positively to the activity.Conclusion: These findings indicate that training in developing SPS assessments integrating the Smart Performance Assessment (SAPA) platform, Canva, and ChatGPT has proven effective in strengthening teachers' competencies, both conceptually and practically, thereby supporting improvements in the quality of science learning.